Poverty - Lister, Ruth, 1949- (Cambridge, U.K. : Polity Press, 2021)
"The essential introduction to a persistent social ill"--
Machine generated contents note: Concepts, definitions and measures -- Why concepts matter -- Chapters and themes -- 1. Defining Poverty -- Approaches to defining poverty -- Beyond the absolute -- relative dichotomy -- Conclusion -- 2. Measuring Poverty -- `Why?' and `how?' questions -- `What?' questions -- `Who?' questions -- Conclusion -- 3. Inequality, Social Divisions and the Differential Experience of Poverty -- Inequality, social class and polarization -- The experience of poverty -- Gender -- `Race' and ethnicity -- Disability -- Age -- Geography -- Conclusion -- 4. Discourses of Poverty: From Othering to Respect -- Othering and the power of discourse -- Rooted in history -- Labelling in the late twentieth and the twenty-first century -- The `p' words -- Representations of poverty -- Stigma, shame and humiliation -- Dignity and respect -- Conclusion -- 5. Poverty and Agency: From Getting By to Getting Organized -- Agency -- Getting by -- Getting (back) at -- Getting out -- Getting organized -- Conclusion -- 6. Poverty, Human Rights and Citizenship -- Human rights -- Citizenship -- Voice -- Power not pity' -- Conclusion -- Key themes -- Research, policy and practice -- A politics of redistribution and recognition&respect.
Includes bibliographical references and index.
Keywords: Poverty